Dispersion and self-orientation of gold nanoparticles in sol–gel hybrid silica – optical transmission properties. Issue 5 (5th December 2014) - Lundén, H.; Liotta, A.; Chateau, D.; Lerouge, F.; Chaput, F.; Parola, S.; Brännlund, C.; Ghadyani, Z.; Kildemo, M.; Lindgren, M.; Lopes, C.
Abstract : An original method for surface modification of metal nanoparticles and insertion in sol–gel monoliths is reported. The optical characterizations show the particle self-orientation in the bulk. Abstract : Silica-based hybrid materials doped with gold nanoparticles (AuNPs) of different shapes were prepared with an adapted sol–gel technology (using MTEOS) and polished to high optical quality. Both spherical (23 and 45 nm in diameter) and bipyramidal (36, 50 and 78 nm in length) AuNPs were prepared and used as dopants. The AuNPs were functionalized with a novel silicone polymer for compatibilization with the sol–gel medium. The glass materials showed well defined localized surface plasmon resonance (SPR) absorbance from the visible to NIR. No redshifts in the spectra, due to the increase in doping concentration, were observed in the glasses, proving that no or very small SPR coupling effects occur. Spectroscopic Muller Matrix Ellipsometry showed that the shorter bipyramidal AuNPs (36 and 50 nm in length) have a clear preferred orientation in the MTEOS matrix, i.e. a tendency to be oriented with their long axis in the plane parallel to the glass surfaces. Dispersions of AuNPs have proven to be good optical power limiters that depend on particle size and geometry. The solid-state glass materials showed good optical power limiting at 532 nm for nanosecond pulses, which did not depend on the size or geometry of the AuNPs. In contrast to the observation at 532 nm, at 600 nm no optical limiting effect was observed. In these solids, as for dispersions of AuNPs, the optical limiting response is caused by scattering.